Pyoderma Gangrenosum in a Splenectomy Incision in a Patient with Haemolytic Anaemia due to Hereditary Spherocytosis: a Case Report and Literature Review - Piotr K. Krajewski (Society for Publication of Acta Dermato-Venereologica, 2021)
Abstract is missing (Short communication)